Cholesterol Metabolism: A Double-Edged Sword in Hepatocellular Carcinoma - Zhou, Fangli; Sun, Xiaoli (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) represents a leading cause of cancer-related deaths globally. The rising incidence of metabolic syndrome and its hepatic manifestation, nonalcoholic fatty liver disease (NAFLD), have emerged as the fastest-growing cause of HCC in recent years. Cholesterol, a major lipid component of the cell membrane and lipoprotein particles, is primarily produced and metabolized by the liver. Numerous studies have revealed an increased cholesterol biosynthesis and uptake, reduced cholesterol exportation and excretion in HCC, which all contribute to lipotoxicity, inflammation, and fibrosis, known HCC risk factors. In contrast, some clinical studies have shown that higher cholesterol is associated with a reduced risk of HCC. These contradictory observations imply that the relationship between cholesterol and HCC is far more complex than initially anticipated. Understanding the role of cholesterol and deciphering the underlying molecular events in HCC development is highly relevant to developing new therapies. Here, we discuss the current understanding of cholesterol metabolism in the pathogenesis of NAFLD-associated HCC, and the underlying mechanisms, including the roles of cholesterol in the disruption of normal function of specific cell types and signaling transduction. We also review the clinical progression in evaluating the association of cholesterol with HCC. The therapeutic effects of lowering cholesterol will also be summarized. We also interpret reasons for the contradictory observations from different preclinical and human studies of the roles of cholesterol in HCC, aiming to provide a critical assessment of the potential of cholesterol as a therapeutic target.